SYSTEMATIC REVIEW OF PENTAGLOBIN EFFICACY IN PREVENTING MORTALITY IN NEWBORNS AND OLDER CHILDREN WITH BACTERIAL INFECTIONS AND SEPSIS - V. K. Fedyaeva; O. Yu. Rebrova (Фармакоэкономика)
Objectives. There is no consistent evidence of clinical efficacy of Pentaglobin for reducing mortality in newborns and older children with bacterial infections and sepsis. The aim of the study was to update evidence by considering recent clinical trials and analyzing age populations and comparators separately.Methods. We searched publications in PubMed and the Cochrane Library in December 2014 and in October 2015. All-cause mortality was analyzed, and systematic review using meta-analysis and indirect comparison was carried out.Results. Three meta-analyses and 7RCTs were considered, including 6 trials studied the effect of Pentaglobin in newborns, and one in children 1-24 months old. All interventions were applied with basic therapy (BT). In newborns mortality is lower in Pentaglobin than in all comparators groups, RR 0.51 [0.32; 0.82], and in BT with or without placebo, RR 0.56 [0.34; 0.91]. Children under 24 months receiving Pentaglobin also had lower mortality than in all comparators group, RR 0.51 [0.36; 0.72]. Indirect comparison of IgM and IgG in adults showed no differences, in newborns the difference is in favor of IgM, RR 0.51 [0.32; 0.82].Conclusion. Pentaglobin is effective in reducing all-cause mortality in newborns with bacterial infection or sepsis in comparison with any comparators (BT with or without placebo, albumin, IgG), in children under 24 months in comparison to BT with or without albumin. Further head-to-head clinical trials are needed to enhance evidence.